Naming as a strategy for identity construction in selected 21st century Nigerian novels - Tayo Lamidi,; Romanus Aboh, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2011)
Although studies within linguistics are quick to demonstrate how language constructs identity, little attention has been given to the symbolic uses of names in the construction of identity in Nigerian novels, and this tends to undermine the fundamental role of lexis such as names in the construction of identity. The present study therefore employs Castells’ identity framework to investigate how names are a linguistic resource for identity construction in selected 21st-century Nigerian novels. Four novels by Nigerian authors representing the four geographical zones of Nigeria were purposefully sampled. The analysis is both quantitative and qualitative. The study illustrates that identity is an incoherent concept, revealing that the study of identity requires the application of systematic and methodological approaches